2021
DOI: 10.1001/jama.2020.27205
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Bicuspid Aortic Valve and Associated Aortopathy in Newborns in Copenhagen, Denmark

Abstract: IMPORTANCEThe prevalence and characteristics of bicuspid aortic valve (BAV) are mainly reported from selected cohorts. BAV is associated with aortopathy, but it is unclear if it represents a fetal developmental defect or is secondary to abnormal valve dynamics.OBJECTIVE To determine the prevalence of BAV and BAV subtypes and to describe the associated aortopathy in a large, population-based cohort of newborns. DESIGN, SETTING, AND PARTICIPANTS The Copenhagen Baby Heart Study was a cross-sectional, population-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…In addition, we found that more than three times as many mothers of fetuses with BAV smoked prior to pregnancy compared with mothers of fetuses with a normal aortic valve, which was also similar to findings of the primary work of CBHS 1 . From oncological research, it has been proposed that smoking alters the Notch signaling pathway, which is essential in embryogenesis and which regulates cell life and cardiovascular development processes 20 .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In addition, we found that more than three times as many mothers of fetuses with BAV smoked prior to pregnancy compared with mothers of fetuses with a normal aortic valve, which was also similar to findings of the primary work of CBHS 1 . From oncological research, it has been proposed that smoking alters the Notch signaling pathway, which is essential in embryogenesis and which regulates cell life and cardiovascular development processes 20 .…”
Section: Discussionsupporting
confidence: 86%
“…As illustrated in Figure 2, the diameters of the aorta and pulmonary artery were generally larger in fetuses with BAV, but all within the general distribution of the values in controls. Although there was a significant difference in the aorta and pulmonary artery diameters between fetuses with BAV and controls, in line with the neonatal findings in this cohort 1 , the statistical significance of the difference was lost following Bonferroni correction of the P-values, in contrast to the neonatal findings. Hence, the Bonferroni correction may have imposed a Type-II error in the present study, which had a smaller sample size than the neonatal study.…”
Section: Discussionsupporting
confidence: 80%
“…Bicuspid aortic valve has been described as one of the common cardiac congenital defects. Its prevalence is estimated to be between 0.5% and 2% in the general population [4]. Bicuspid aortic valve is associated with the risk of developing many cardiac complications such as aortic stenosis, aortic dissection, and endocarditis [4].…”
Section: Discussionmentioning
confidence: 99%
“…Bicuspid aortic valve (BAV) is the most common congenital heart valve disease, and the burden of BAV disease is greater than for other congenital anomalies (1)(2)(3). BAV can present in diverse spectrum and affect valve function from non-dysfunctional to severe aortic stenosis (AS) or severe aortic regurgitation (AR) (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%